Enhancing employee financial capability via super-apps: A case study in Semarang - Sri Suyati; Nurchayati Nurchayati; Janti Soegiastuti (Annals of Human Resource Management Research, 2025)
Purpose: Digital transformation has driven the development of technology-based financial services, including super-apps that integrate various services in one platform. This study aims to analyze the effect of super-apps usage and digital literacy on people's financial behavior, with financial inclusion as a mediating variable. Research Methodology: This study uses a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis technique. Respondents were 194 people from Semarang City who were active users of super-apps services. Results: The results of the study show that the use of super-apps and digital literacy have a positive effect on financial behavior, both directly and indirectly through financial inclusion. Digital literacy is proven to have the strongest influence on financial inclusion, which then significantly mediates the relationship between digital literacy and financial behavior. Meanwhile, the indirect effect of super-apps usage on financial behavior through financial inclusion is relatively small. Conclusions: These findings emphasize the importance of increasing digital literacy to encourage broader financial inclusion and wiser financial behavior. Limitations: This study is limited to a sample of 194 respondents in Semarang, so the findings cannot be widely generalized. The use of self-report questionnaires may introduce bias. The variables examined are still limited, and the cross-sectional design cannot explain causal relationships. In addition, the study does not differentiate types of super-apps and does not consider structural factors such as income and digital infrastructure. Contribution: May consider adding variables such as trust in fintech, personal financial efficacy, or digital security risks.